Democracy and Political Parties: A Brief Survey around the World and in Nepal - Hachhethu, Krishna (Journal of Political Science, 2025)
Democracy, a political system that has experienced significant changes over time, existed before the rise of political parties. Samuel Huntington classifies the evolution of democracy into three primary waves. The First Wave, spanning the 17th to the 19th centuries, emphasized civil and political rights, establishing the foundation for liberal democracy and its related institutions. The Second Wave, following World War II, witnessed the dissemination of democratic principles to Asia, Africa, and Latin America as a result of decolonization. Nonetheless, this wave faced challenges, including ethnic tensions and ineffective governance. The Third Wave, during the late 20th century, saw a revival of democratic practices across multiple developing countries, highlighting the importance of inclusive governance. Nepal's path to democracy began in 1951 following the conclusion of the Rana regime; nonetheless, authoritarian rule and internal strife have impeded its advancement. At present, attention is directed towards establishing an inclusive democracy capable of effectively managing ethnic diversity and enacting governance reforms. Political parties, which were originally formed based on ideological principles, have significantly transformed into electoral organizations mainly aimed at securing power. These parties face challenges like centralization, insufficient internal democratic processes, and a growing gap between themselves and the electorate. Suggested reforms aim to improve representation, implement term limits for leaders, and enhance grassroots candidate selection.